Initial Evaluation of the Acute and Chronic Multiple Ligament Injured Knee - Vinyard, Timothy Ryan; Boyd, Joel; MacDonald, Peter B. (The Journal of Knee Surgery, 2012)
Multiple ligament injuries of the knee are rare, and severe injuries are often present following a knee dislocation. Appropriate initial evaluation and management is of critical importance for maximizing the potential outcome and avoiding disastrous consequences associated with these difficult injuries. While many of these injuries present acutely in an emergency department or clinic, presentation on a delayed basis is not uncommon. Injuries can present in a variety of situations, such as an isolated knee injury in an athlete or as part of a multisystem-injured trauma patient. In this publication, we review the etiology, classification, and comprehensive initial evaluation of the acute and chronic multiple-ligament injured knee.
Keywords: knee dislocation; multiligament knee injury; evaluation; peroneal nerve injury; popliteal artery injury; posterolateral corner injury